2016
DOI: 10.1242/dmm.025536
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene expression patterns critically involved in experimental autoimmune encephalomyelitis and multiple sclerosis

Abstract: After encounter with a central nervous system (CNS)-derived autoantigen, lymphocytes leave the lymph nodes and enter the CNS. This event leads only rarely to subsequent tissue damage. Genes relevant to CNS pathology after cell infiltration are largely undefined. Myelin-oligodendrocyte-glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE) is an animal model of multiple sclerosis (MS), a chronic autoimmune disease of the CNS that results in disability. To assess genes that are involved in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…In a recent report, Herrmann et al (2016) demonstrated that CD38 was crucially involved in the pathology of EAE. CD38 expression was strongly elevated both in the encephalitogenic lymph node (LN) cells and in the CNS-infiltrating cells after induction of EAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent report, Herrmann et al (2016) demonstrated that CD38 was crucially involved in the pathology of EAE. CD38 expression was strongly elevated both in the encephalitogenic lymph node (LN) cells and in the CNS-infiltrating cells after induction of EAE.…”
Section: Discussionmentioning
confidence: 99%
“…In pathological conditions, CD38 has been reported to be involved in the activation of microglia and astrocytes in mouse models of glioma and traumatic brain injury, and human HIV-infected brains (Kou et al, 2009; Levy et al, 2009, 2012). However, the role of CD38 in demyelination is still unclear, although its involvement in the modulation of T-cell activation was reported in the experimental autoimmune encephalomyelitis (EAE), another widely used animal model of MS (Herrmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has recently characterized CD38 as a marker that is increased in inflammatory murine bone marrow-derived M(LPS + IFN-γ) macrophages and decreased in M2 macrophages compared to untreated M0 macrophages ( 47 ). CD38 upregulation is also observed in a sepsis model ( 47 ) as well as Experimental Autoimmune Encephalomyelitis (EAE), the mouse model of MS ( 48 ). Given that CD38 is a surface marker that allows live cell sorting for downstream applications, it provides an advantage over intracellular markers such as iNOS.…”
Section: Macrophage/microglia Phenotypes Function and Nomenclaturementioning
confidence: 99%
“…This effect seems paradoxical since CD38 KO mice showed deficits in various learning and memory tasks such as the Morris water maze, contextual fear conditioning, and the object recognition test [65]. In the experimental autoimmune encephalomyelitis mouse model of multiple sclerosis, CD38 deletion reduced disease severity [66]. Note that CD38 deletion was also shown to suppress glial activation and neuroinflammation in a mouse model of demyelination induced by cuprizone administration, an effect that was most likely due to enhanced level of NAD in CD38 KO mice [67].…”
Section: Cd38 Involvement In Neurodegeneration and Neuroinflammationmentioning
confidence: 99%